Synthesis of Graduate Education Theses Focused on Teachers' Views on Inclusive Education in Turkey: A Meta-Ethnographic Study - Gülcihan Hasanoğlu Yazçayır; Hasan Gürgür (Anı Publishing, 2019)
A high number of both qualitative and quantitative research studies have been conducted on inclusion practice in Turkey. In postgraduate theses focusing on inclusion practice via a qualitative design to comprehensively describe and understand the issue, the goal is mostly to determine teachers' opinions. The aim of this research, on the other hand, is to examine postgraduate theses investigating the opinions of teachers who work in inclusion classes. For this purpose, five researches were focused. It has been designed in line with meta-ethnography design to study the postgraduate theses conducted in Turkey employing semi-structured interviews-one of the qualitative data collection techniques. A comparative and exploratory analysis process has been administered to identify the shared and different themes in the aforementioned studies. Accordingly, three themes have been determined, which are a) current situation of inclusion practice, b) problems in inclusion practice, and c) teachers' expectations as to improving the quality of inclusion practice. Based on the findings of research studies completed around inclusion practice and teachers' opinions, it is possible to conclude that there is a need for development-centered action research at inclusion schools and classes.